1998
DOI: 10.1074/jbc.273.8.4718
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 Receptor-mediated Modulation of Dopamine D1 Receptors in Stably Cotransfected Fibroblast Cells

Abstract: It has been shown that the binding characteristics of one type of G protein-coupled receptor can be altered by the stimulation of another type of G protein-coupled receptor in crude membrane preparations (1). Such intramembrane interactions have been postulated to represent direct interactions between the receptor molecules and/or to involve G proteins or other mobile molecules associated with the membrane (1). There is increasing evidence suggesting that antagonistic intramembrane interactions between specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 21 publications
2
77
0
Order By: Relevance
“…The reduction in adenosine affinity in transfected cells suggests that the latter possibility is more plausible, as a higher K d was detected. In addition, cross-talk between heterodimeric receptor pairs can modify positively or negatively the response to agonists resulting in either enhanced-G-protein activation or cross-inhibition (Ferre et al 1998, Jordan & Devi 1999, even changes in G-protein-coupling specificity (George et al 2000). In this particular case, the presence of GHS-R1a in HEK 293 cells appears to be essential for the qualitative coupling of A2b-R and A3-R to G s -signaling pathway, as cAMP levels were elevated in response to adenosine in HEK-GHS-R1a cells, whereas no increase was determined in HEK 293 cells .…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in adenosine affinity in transfected cells suggests that the latter possibility is more plausible, as a higher K d was detected. In addition, cross-talk between heterodimeric receptor pairs can modify positively or negatively the response to agonists resulting in either enhanced-G-protein activation or cross-inhibition (Ferre et al 1998, Jordan & Devi 1999, even changes in G-protein-coupling specificity (George et al 2000). In this particular case, the presence of GHS-R1a in HEK 293 cells appears to be essential for the qualitative coupling of A2b-R and A3-R to G s -signaling pathway, as cAMP levels were elevated in response to adenosine in HEK-GHS-R1a cells, whereas no increase was determined in HEK 293 cells .…”
Section: Discussionmentioning
confidence: 99%
“…Whether both sites are indeed functional and whether ligand binding to both sites is necessary for receptor activation are critical questions to understand the activation mechanism of GPCRs. 125 [␦ and opioid (Jordan and Devi, 1999), and ␦ opioid (George et al, 2000), somatostatin sst1 and sst5 receptors (Patel et al, 2002), adenosine A1 and dopamine D1 (Ferre et al, 1998), somatostatin sst5, and dopamine D2 (Rocheville et al, 2000a)]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Lindskog et al (2002) reported that caffeine through its effect on A 2A receptors increases the state of phosphorylation of DARPP-32, indicating a new mechanism for the postsynaptic interaction between dopamine and adenosine A 2A receptors that might produce long-term postsynaptic changes. Caffeine sensitization and amphetamine cross-sensitization O Cauli et al Antagonistic interactions between dopamine D 1 and adenosine A 1 receptors have been demonstrated at both receptor and behavioral levels (Ferré et al, 1998;Gines et al, 2000;Popoli et al, 1996). These types of interactions, however, have been shown to play a pivotal role in limbic rather than in motor areas (Bonci and Williams, 1996;Kuzmin et al, 1999;Mayfield et al, 1999), whereas in turning behavior, A 1 receptor antagonists do not appear to play a central role (Pinna et al, 1996).…”
Section: Turning Behavior and Dopamine Release After Subchronic Caffeinementioning
confidence: 99%